Requirements engineering (RE) for social good: RE cares - Dekhtyar, Alexander; Paech, Barbara (IEEE software, 2019)
As researchers and teachers and practitioners, we “software types” excel at multitasking. This, in part, led us to ask the question: Can one attend a software engineering conference and do something good for society? We found the answer to be a resounding yes. In this article, we present our first experience of running RE Cares, a conference collocated event. This event included a workshop, conference sessions, and a hackathon for developing an application to support emergency field activity for Mutual Aid Alberta, a nonprofit organization coordinating natural disaster responses in the Canadian province.